CLASSIFICATION OF DIGITALIZATION OF PRODUCTION AND BUSINESS PROCESSES - CHUIENKO, VITALII; TAZETDINOV, VALERII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The digital transformation of enterprises is impossible without the digitalization of their business processes. A business process is a chain of actions that leads to the creation of a product or the provision of a service. It is the basis of any enterprise. In order to develop scientific knowledge about business processes, it is necessary to constantly analyze information, group it or systematize it into a single whole. This will improve the performance of enterprises and successfully carry out digitalization in every industry, including the agro-industrial complex. The article proposes a classification of digitalization of production and business processes by areas of implementation and types of process optimization. In particular, the types of production process optimization are considered in the agro-industrial complex. The main results are that for the first time a classification of digitalization of production and business processes, including in the agro-industrial complex, has been developed. To form the classification, the scientific works and textbooks of scientists in the field of business process digitalization management were used. Digitalization enables small companies to create new products and bring them to market quickly. It allows to transform business, create completely new forms of entrepreneurship, modernize the entire society, and move to its digital form. In order to make a management decision on the digitalization of business processes, it is necessary to analyze the existing business processes of an enterprise. The introduction of digitalization at enterprises improves business processes that increase the competitiveness of products. The transition of agricultural enterprises to e-agriculture can be ensured by the use of modern digital technologies, such as computers, servers, websites that allow the transfer and receipt of information on the agricultural sector and markets for agricultural products, raw materials, etc. The classification makes it possible to delineate production processes and constantly improve them, because a business process is a sequence of actions that result in the creation of a new product, service or analysis of employee performance.